Iterative signal detection to mitigate ISI and MUI for diffusion-based molecular communications - Thakur M.S.; Sharma S.; Bhatia V. (My University, 2025)
Molecular communication via diffusion (MCvD) where bio-molecules carry information is a most promising and viable solution for communication between nanoscale devices. However, slow moving molecules cause inter-symbol-interference (ISI) which is one of the major impediments in MCvD systems. In this work, a novel iterative block-wise non-coherent signal detection method is proposed to mitigate the ISI at the receiver. Since the proposed method does not require the channel state information at the receiver, this reduces the molecular communication system's complexity. The bit error rate (BER) performance of the proposed iterative detection method is evaluated in the presence of both ISI and counting noise. Substantial improvement in MC system's BER performance is observed by using the proposed detection method as compared to conventional approach. Furthermore, effectiveness of the proposed scheme is also analyzed in the presence of multiuser interference. © 2021 Elsevier B.V.